Characterisation of ionic polymer metallic composites as sensors in robotic finger joints. (4th December 2009) - Chew, X.J.; Van den Hurk, A.; Aw, K.C.
Ionic polymer metallic composite (IPMC) is a smart material that has been proposed for use in applications such as measuring joint motion in a robotic hand or data glove; where minimising size, weight and cost is a top priority. The general sensing characteristics of IPMC have been reported, but at this stage a comprehensive model for the practical application of IPMC sensors does not exist. In this paper, a simple model of the sensor's response to rotary joint motion is proposed, based on experimental findings. The testing apparatus used in this study was designed and built to closely relate to the geometries and movement of a human finger joint. The performance of the model was checked through a series of verification tests over a range of joint motions. The results show that the model is reasonably accurate, with the angle being calculated to within 3% of the actual value over most of the tested range of motions.